PENGEMBANGAN BUPENA BERBASIS PENDEKATAN STM (SAINS TEKNOLOGI MASYARAKAT) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH IPA - Hotma Tiolina Siregar; Rinci Simbolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to describe the results of increasing student problem solving abilities and learning tools in the form of an authentic assessment book (BUPENA) through the community technology science approach (STM), at SD Muhammadiyah 08 Medan, Class 4E, 2020-2021. The data collection tools in this study were validation sheets, problem-solving ability tests, and teacher and student response questionnaires developed through the Community Technology Science Approach (STM) with a modified 3-D model. The population in this study were all Class IV SD SD Muhammadiyah 08 Medan TA 2020-2021, the sample of this study was class IV-E, totaling 30 people. The Science and Technology Community (STM) approach using BUPENA developed in class IV-E SD Muhammadiyah 08 Medan has increased, which can be seen from: 19 students who completed the initial problem solving ability test were 19 people with an average score of 68.67 and increasing to 28 people with an average score of 87.83 on the final problem solving ability test. Then the completeness of classical learning for the initial problem solving ability test, there were 63.33% of students who did not complete and it increased to 93.33% of students who completed the final problem solving ability test.Keywords: BUPENA Development, STM Approach, IPA